Regional frequency analysis of extremes precipitations in Northern of Mozambique - M. Álvarez; J. Puertas; E. Peña (Ingeniería del Agua)
Extreme precipitation events that occur over internal basins of Cabo Delgado (Northern Mozambique) often result in the occurrence of flood events with associated loss of life and infrastructure. This paper presents a study of regional frequency analysis of maximum daily precipitations based on the index flood procedure with estimated parameters by L-moments approach. Observed annual maximum daily precipitation series of 12 stations with records of more than 20 years were analyzed. The discordancy and heterogeneity measures based on the L-moments suggest that the region can be considered as homogeneous. Among the candidate distributions analyzed Monte Carlo simulations identified the Generalized Logistic distribution function as the best regional fit for the region. The achieved results will be useful in hydrologic and hydraulic studies related to floods and floodplain delineation in the region.